The Effect of Health Education Using Menstruation Magic Spin Wheel on Elementary School Girls' Knowledge about Menarche in Sangkanayu, Purbalingga - Azzahra, Fathimah; Azizah, Atika Nur (Proceedings Series on Health & Medical Sciences, 2025)
Menarche, or the first menstrual period, is a key milestone of puberty in adolescent girls. A lack of knowledge about menarche may lead to anxiety, unpreparedness, and inappropriate personal hygiene practices. Interactive media-based health education has emerged as an effective strategy to enhance understanding among elementary school students. This study aimed to examine the effect of health education using the Menstruation Magic Spin Wheel on the level of knowledge regarding menarche among elementary school girls. This study employed a quasi-experimental design with a nonequivalent control group. The population included all female students from SD Negeri 1 Sangkanayu and SD Negeri 2 Sangkanayu, Mrebet Sub-district, Purbalingga Regency. A total of 68 respondents were divided into an intervention group (n = 34) and a control group (n = 34). Data were analyzed using the Wilcoxon Signed Rank Test. The Wilcoxon test showed a significant increase in knowledge levels in the intervention group before and after receiving health education (p 0.001). In contrast, no significant difference was observed in the control group (p 0.05). Health education using the Menstruation Magic Spin Wheel was effective in increasing elementary school girls knowledge about menarche. Interactive and engaging educational media can serve as a child-friendly alternative for delivering health education.